Public Health Impacts of Climate Change in Nepal - Joshi, H D; Dhimal, B; Dhimal, M; Bhusal, C L (Journal of Nepal Health Research Council, 2011)
Climate change is a global issue in this century which has challenged the survival of living creatures affecting the life supporting systems of the earth: atmosphere, hydrosphere and lithosphere. Scientists have reached in a consensus that climate change is happening. The anthropogenic emission of greenhouse gases is responsible for global warming and therefore climate change. Climate change may directly or indirectly affect human health through a range of pathways related to temperature and precipitation. The aim of this article is to share knowledge on how climate change can affect public health in Nepal based on scientific evidence from global studies and experience gained locally. In this review attempt has been made to critically analyze the scientific studies as well as policy documents of Nepalese Government and shed light on public health impact of climate change in the context of Nepal. Detailed scientific study is recommended to discern impact of climate change on public health problems in Nepal. Keywords: cardio-respiratory, climate change, injuries, malnutrition, psychological stress, public health, vectorborne diseases.